THE EFFECT OF SOCIAL INTERACTION OF THE FISHERMAN COMMUNITY ON THE STRATIFICATION OF COASTAL COMMUNITIES OF SABARU VILLAGE, LIUKANG TAGAYA DISTRICT, PANGKEP REGENCY - Arpandi Arpandi (Universitas Negeri Makassar, 2022)
This study aims to find out 1) The description of the social interaction of the fishing community in the coastal community of Sabaru Village, Liukang Tangaya District, Pangkep Regency 2) The description of the stratification of the coastal community of Sabaru Village, Liukang Tangaya District, Pangkep Regency. 3) The description of the social interaction of the fishing community towards the stratification of the Sabaru village community, Liukang Tangaya District, Pangkep. This study uses quantitative research with a population of 160 fishing communities. The results show that 1) The description of the social interaction of the fishermen community in the village of Sasusu, Liukang Tangaya District, Pangkep Regency is in the